PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA MATERI LUAS BANGUN DATAR MENGGUNAKAN MODEL SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS (STEM) DI KELAS V SDN 49 KURANJI KOTA PADANG (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the low learning outcomes of fifth-grade students at SDN 49 Kuranji, Padang City, caused by limited student engagement, suboptimal selection of learning models and methods, and the preparation of teaching modules that are not fully aligned with the deep learning–based Independent Curriculum. In addition, the learning process remains teacher-centered. This study aims to improve students’ learning outcomes in the topic of the area of plane figures through the implementation of the Science, Technology, Engineering, and Mathematics (STEM) model. This research employs Classroom Action Research (CAR) using both qualitative and quantitative approaches, conducted in three cycles consisting of planning, implementation, observation, and reflection. Data were collected through test and non-test techniques, including the assessment of teaching modules, the learning process, and students’ learning outcomes. The subjects of this study were teachers and fifth-grade students at SDN 49 Kuranji, Padang City. The results indicate consistent improvement in each cycle. The evaluation of teaching modules increased from 93.75% in Cycle I to 95.83% in Cycle II and reached 100% in Cycle III. Teacher activity improved from 85.47% in Cycle I to 92.82% in Cycle II and 96.32% in Cycle III. Student activity also increased from 83.93% in Cycle I to 89.28% in Cycle II and 96.42% in Cycle III. Furthermore, students’ learning outcomes improved, with the average score rising from 77.03 in Cycle I to 83.37 in Cycle II and 89.64 in Cycle III, achieving 100% mastery.